A Spatial Political-Economic Review on Urban Growth in Java under Economic Liberalization of Dutch Colonialism During the 19th Century - Hafid Setiadi; Hadi Sabari Yunus; Bambang Purwanto (Indonesian Journal of Geography, 2022)
This study understands the rise and fall of cities as a result of colonial worldview and practices. Based on spatial political-economic thinking, this study examines the spatial implications of Dutch colonialism on urban growth in Java during the 19th century. The practice of colonialism at that time took place in a relatively stable regional situation.  The analysis of textual data from various literature indicates that the economic liberalization of Dutch colonialism in that time was a continuation of the VOC’s mercantilism but with a stronger intention to control the factors of production. Territorial expansion to fertile areas indeed encouraged the emergence of medium-sized cities in the inland, but on the other hand, degenerated several older cities on the coast. Spatially, the ambitions and practices of colonialism had a limited implication on urban growth. The combination of territorial and capital logic triggered political liquidation which was reflected in the spatial pattern of urban growth. The identity and symbol of colonial power were attached as new elements to the cities. This process revealed a locational decision to channel economic benefits to strategic places for sustaining domination of power for the long-term.